2018
DOI: 10.1002/chem.201705022
|View full text |Cite
|
Sign up to set email alerts
|

2,2′‐Bipyridine Equipped with a Disulfide/Dithiol Switch for Coupled Two‐Electron and Two‐Proton Transfer

Abstract: [1,2]Dithiino[4,3-b:5,6-b']dipyridine (1) and its protonated open form 3,3'-dithiol-2,2'-bipyridine (2) were synthesised and their interconversion investigated. The X-ray structure of 2 revealed an anti orientation of the two pyridine units and a zwitterionic form. In depth electrochemical studies in combination with DFT calculations lead to a comprehensive picture of the redox chemistry of 1 in the absence and presence of protons. Initial one-electron reduction at E =-1.20 V results in the formation of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(62 citation statements)
references
References 33 publications
(40 reference statements)
5
57
0
Order By: Relevance
“…Cyclic voltammetry of the PhSSPh reference compound (Scheme 1b) shows the typical features of potential inversion as reported previously for this and closely related compounds (SI page S16). 10,12 From cathodic scans, a peak potential of -1.6 V vs. SCE is measurable, while on return scans the corresponding reoxidation wave is detected at -0.3 V vs. SCE. The shift of 1.3 V between corresponding (two-electron) half-waves is a manifestation of the redox potential inversion.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Cyclic voltammetry of the PhSSPh reference compound (Scheme 1b) shows the typical features of potential inversion as reported previously for this and closely related compounds (SI page S16). 10,12 From cathodic scans, a peak potential of -1.6 V vs. SCE is measurable, while on return scans the corresponding reoxidation wave is detected at -0.3 V vs. SCE. The shift of 1.3 V between corresponding (two-electron) half-waves is a manifestation of the redox potential inversion.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Recently, the molecule 3,3 ′ -disulfide-2,2 ′ -bipyridine (SSbpy), with a functional disulfide bridge, was synthesized for the first time showing interesting redox capabilities (Cattaneo et al, 2018). The redox active dithiol/disulfide switch coupled to proton transfer provides the ligand with promising properties for heterogenization as well as multi-electron storage and redox control.…”
Section: Introductionmentioning
confidence: 99%
“…109 In non-proton-coupled redox reactions, every additional redox step is usually thermodynamically less favored than the preceding step, except in the somewhat special cases of redox potential inversion. 71,72,[74][75][76]110 As noted in the introduction, temporary storage of redox equivalents is needed to synchronize the fast primary photoinduced electron transfer events with the slower multi-electron turnovers in catalytic reaction centers, but there is also the important issue of photon flux. Two-electron transfer is difficult to induce upon single excitation.…”
Section: Discussionmentioning
confidence: 99%
“…5d), for which it was found that water triggers redox potential inversion due to protonation of the radical monoanion at its basic N-atom. 76 It will be interesting to see how that bpy ligand behaves electrochemically and photochemically when coordinated to a metal center.…”
Section: Pcmet In Molecular Donorbridge-acceptor Compoundsmentioning
confidence: 99%
See 1 more Smart Citation